Hubungan Kualitas Program Siaran dengan Aspek Kognitif Pendengar Radio - Dias Arliadini; Nova Yuliati (UNISBA Press, 2022)
Abstract. The quality of broadcast programs is one of the factors that can influence audiences to be interested in programs made by radio stations. Broadcast programs must always be directed and made according to the needs of the community, one of which is the needs of the cognitive aspects of the audience. How the mass media (radio) will help the audience to get and understand any information it receives. The purpose of this study was to determine the relationship between the quality of broadcast programs which include compatibility, consevation of program resources, and breadth of appeal of the